Recruitment Pattern Of Blue Swimming Crab Portunus pelagicus in Salemo Island Waters, South Sulawesi Province. - Nurdin, Muh. Saleh; Hasanah, Nur; Putra, Aswad Eka (FAPETKAN UNTAD, 2019)
This research aims to analyze yield per recruitment of the blue swimming crabs caughtin Salemo Island. This research was conducted from March to July 2015. Yield per recruitment ofthe blue swimming crab was analysed by using FISAT II. The research results indicated thatrecruitment pattern throughout the year with one peak, percentage of yield per recruitment 1.90-22.11 %.Keyword: blue swimming crab, yield per recruitment, Salemo Island.